PENGEMBANGAN PROGRAM DESA WISATA BERBASIS JEJARING BISNIS DI DESA TAMANSARI KABUPATEN BANYUWANGI - Safrieta Jatu Permatasari (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2022)
A tourism village is an integrated tourism concept in an area that combines local tourism potential in the form of art-culture products and natural beauty, accommodation, and other supporting facilities. Tourist villages have great potential, especially for the tourist segment who is interested in exploring the rich arts and culture of the foreign community. This study analyzes the development of a business network-based tourism village program in Tamansari Village, Banyuwangi Regency, namely by cooperating with the private sector to improve the community's economy through the concept of a tourist village. Using corporate social responsibility (CSR) funds from private companies, several tourist sites in Tamansari village were developed, starting from the milk village (Dusun Ampel Gading), the mining village, to the flower village (Dusun Jambu). Qualitative descriptive method is carried out with data collection techniques used are observation, interviews with village heads and Pokdarwis, as well as literature study. The results showed that the development of a business network-based tourism village program in Tamansari Village had a significant impact on boosting the residents' economy, and could be used as additional village income through APBDes. The village government in supporting the development of tourist villages collaborates with Pokdarwis (Tourism Awareness Groups), which have an important role and contribution to explore new potential in tourism development. thorough. Keywords: Development; Tourism Village Program;, and Business Network